Clil in Genetics: Class Activity and English Language Usage in Classroom - Kaewngam, Soravis; Chauvatcharin, Nopmanee; Kewara, Punwalai (Scholar: Human Sciences, 2020)
Utilization of the English language to access scientific knowledge is essential to learning. Therefore, many schools have developed the Integrated English Program (IEP), to enable students to develop both academic content and language skill. Teaching genetics by using English as a medium, is challenging for non-native English speaking teachers as there are many specialized terms in the content to be delivered. Students’ confidence in using the language in authentic situations seem low and learner engagement is often lacking in such traditional educational settings. The purpose of this study is to investigate how content and language integrated learning (CLIL) impact on student’s attitudes, learning achievement and use English of students' when applying CLIL in teaching Genetics. The class activities were designed as six steps in delivering the program. The result indicates that both learner engagement and students’ confidence in using the language are characteristic. It can also be noted that content integration, with extensive focus on authentic materials and cooperation, promote language development. As well as learning achievement with a higher score after using such integration. Nevertheless, the main challenge outlined by the participants is the language barrier. Hence, planning of the teaching units, as to provide the right support and challenges for the different learners, and to design the tasks so that natural collaboration becomes a key factor for introducing a content integrated collaborative language classroom.